Smoking cessation aids - Roopchandani, Komal; Singhvi, Indrajeet; Kar, Mousumi (Asian Journal of Pharmaceutics (AJP), 2014)
Smoking is a practice where a substance, most commonly tobacco as dried or curled leaves is burned and the smoke is tasted or inhaled. This is primarily done as a recreational activity. But, owing to the chemicals present in tobacco, it slowly becomes addictive in nature. Few smokers use effective smoking cessation aids when trying to stop smoking. Smoking is the most important single cause of morbidity and mortality in under developed, developing and developed countries. Because smoking prevention will not affect tobacco-related mortality, quitting by current smokers is the main way to achieve positive effects on mortality. Many smokers are interested in quitting. Most of the smokers try to quit smoking at least once in their lifetime. To support smokers in their quit attempts, a wide range of smoking cessation aids is available. These comprise methods and products to assist smokers in quitting through coping with psychological or physical aspects of nicotine dependence. Meta-analyses have shown that smoking cessation courses, nicotine replacement therapy, and bupropion can significantly increase success rates in quitting. Even minimal interventions such as self-help materials have a small effect when compared with no intervention.